FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG DENGAN VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR - Afri Sentosa S.; Melanthon Rumapea (Universitas Methodist Indonesia, 2022)
This study aims to determine the effect of free cash flow, management ownership, and institusional ownership to the debt policy with the investment opportunity set as a moderating variable of manufacturing companies listed on the Indonesia Stock Exchange on period 2017 to 2019. Variables used in this research is free cash flow, management ownership, and institusional ownership as an independent variable, debt policy as the dependent variable and the investment opportunity set as a moderating variable. This study was performed on companies listed on the Indonesia Stock Exchange. This research was conducted at 24 companies that meet the criteria of a sampling of 171 companies listed in the Indonesia Stock Exchange. The research data are secondary data from the annual financial statements published 24 companies in Indonesian Stock Exchange.